2012
DOI: 10.1179/1879139512y.0000000014
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of microstructure, microtexture and mechanical properties of linear friction welded IMI 834

Abstract: Titanium alloys have been of great interest in the aerospace industry for many years. Recently, linear friction welding has also been making strides in conquering a part of the aerospace manufacturing market, with its clear advantages over fusion welding and mechanical fastening methods for integrated bladed rotors. High tech near-a alloy IMI834 (Ti-5?8Al-4Sn-3?5Zr-0?7Nb-0?5Mo-0?35Si) was designed to have improved creep resistance and retains its mechanical properties at temperatures up to 600uC. It balances c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 6 publications
5
28
0
Order By: Relevance
“…Understanding their mechanical properties in monotonic and cyclic loadings is fundamental for its industrial application. Several authors studied the tensile properties of similar LFW joints using as PM comparable alloys to Ti6242, such as TA6V and IMI‐834 . Some similar and dissimilar joints failed far from the WCZ .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Understanding their mechanical properties in monotonic and cyclic loadings is fundamental for its industrial application. Several authors studied the tensile properties of similar LFW joints using as PM comparable alloys to Ti6242, such as TA6V and IMI‐834 . Some similar and dissimilar joints failed far from the WCZ .…”
Section: Introductionmentioning
confidence: 99%
“…Several authors studied the tensile properties of similar LFW joints using as PM comparable alloys to Ti6242, such as TA6V and IMI‐834 . Some similar and dissimilar joints failed far from the WCZ . For instance, Dalgaard et al observed that the formation of a fine microstructure in the WCZ of a similar IMI‐834 LFW joint led to a weld overmatch.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The friction between the parts generates heat, which together with the applied force results in a consolidated joint seam with a limited plastically or thermomechanically affected zone (TMAZ). Linear friction welds in titanium alloys exhibit good mechanical properties [4][5][6] as compared to other joining techniques such as laser welding [7], electron beam welding or inertia friction welding [8].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the position in the weldment, different regions of the TMAZ and the base alloy are subjected to different ranges of temperatures and plastic deformation that influence microstructural development. LFW has been successfully used to join steel 5 and titanium alloys 6,7 in applications including manufacturing and repair of turbine components. For Ni-base superalloys, LFW has been used to weld polycrystalline, This joining process is generally considered to be a completely solid-state joining process, 12 and like other friction-welding processes, it could eliminate problems associated with melting and resolidification of conventional fusion welding techniques.…”
Section: Introductionmentioning
confidence: 99%